Pengaruh pH dan Waktu Terhadap Kemampuan Adsorpsi Mip_TFMAA-co-Egdma - St. Fauziah; Nunuk Hariani Soekamto; Muh. Bachri Amran; Paulina Taba (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
A molecularly imprinted polymers (MIP) can be synthesized using functional monomers and template molecules through polymerization with the aid of cross linker. In previous studies, MIP_TFMAA-co-EGDMA was synthesized using the main ingredient tryfluoromethylacrylic acid (TFMAA) as functional monomer, b-sitosterol as a template molecule and ethyleneglycol dimethacrylate (EGDMA) as cross linker. The ability of adsorption against the effects of pH and contact Time of MIP has been evaluated. Variations of pH standard solution b-sitosterol were 4, 5, 6, and 7, while the time variation used were 30, 60, 90, and 120 minutes. The data of b- sitosterol concentrations adsorbed by MIP_TFMAA-co-EGDMA because of the influence of pH and contact times were analyzed using high pressure liquid chromatography (HPLC). pH5 gives the most influence on the adsorption capacity MIP_TFMAA-co-EGDMA against b-sitosterol. The number of b-sitosterol adsorbed on the pH was 1.0265 mg/g, while at 90 minutes was the best time for the MIP b- sitosterol adsorb as much as 1.3486 mg/g. Based on the adsorption kinetics study, the adsorption ability MIP_TFMAA-co-EGDMA against b-sitosterol in accordance with the pseudo second order kinetic model.